Rare Spindle Cell Hemangioma of Bone: A Case Report - Patwardhan, Leena; Sharma, Sunita (Annals of Pathology and Laboratory Medicine, 2023)
Spindle cell haemangioma (SCH), a rare vascular tumour usually appears as a cutaneous nodule and subcutaneous nodules in the extremities in adults in 4 th and 5 th decades of life. Its occurrence in bone and paediatric age group is extremely rare. We report a case of SCH arising at the lateral condyle of femur in a 16 year old female. It is important to avoid misdiagnosis as these lesions are considered to be benign, non neoplastic reactive vascular proliferations, with moderate incidence of recurrence.